ANALYSIS AVAILABILITY OF HOTS INDICATORS ON SENIOR HIGH SCHOOLS PHYSICS EXAM QUESTIONS IN AGAM DISTRICT - Hersha Hanifa; Yenni Darvina; Silvi Yulia Sari; Gusnedi Gusnedi; Silvi Trisna (PILLAR OF PHYSICS EDUCATION, 2022)
Efforts to improve the quality of education in Indonesia continue to be carried out by the Government. One of the ongoing agenda is curriculum development. The 2013 curriculum requires students to have thinking skills, one of which is Higher Order Thinking Skills (HOTS). To achieve this, teachers must practice using strategies to train students to think higher order. It is time to implement HOTS questions in learning. HOTS-based questions can make students skilled in the ability to solve problems, skilled in decision making. The results of the observations show that the questions used in Senior High School throughout Agam Regency are still in the low category and do not meet the good proportion of questions. Therefore, research on the analysis of the HOTS indicator was carried out on physics questions at Senior High School Agam in Agam. This research is descriptive research with a qualitative approach. The population of this research is about Senior High School’s Physics Exam in Agam Regency for the 2019/2020 academic year. The research data was taken using an analytical instrument of question presentation and data collection techniques through documentation. Based on the research that has been done, it is found that the percentage of HOTS indicators for each question is 39.15% for class X semester 1, 38.5% for class X semester 2, 36.3% for class XI semester 1, 18.25% for class XI semester 2 and 24.5% for class XII semester 1 and for HOTS indicators that are often found in Physics Exam questions are the Problem Solving and Critical Thinking indicators, followed by decision making indicators while the least encountered is the Creative Thinking indicator.